COMPARISON OF AMBULATORY AND HOME BLOOD PRESSURE TELEMONITORING WITH PHYSICAL INACTIVITY MONITORING. (June 2022) - Muzik, Jan; Peleska, Jan; Holubova, Anna; Camek, Rene; Navratil, Vojtech; Fiala, Dominik; Doksansky, Marek; Hana, Karel; Vranka, Jakub; Hronova, Julie; Chrolenko, Anna; Jiravova, Maria; et al.
Abstract : Objective: Combined use of office BP (OBP) and out-of-office BP evaluation (ABPM or HBPM) is recommended according to recent guidelines. Aim of the study was to compare the results of BP measurement (BPM) by these methods while improving reliability of HBPTM by the physical activity monitoring. Design and method: BP monitor For a P30Plus was used both for office BP and 3 months home BP telemonitoring (HBPTM) study in triplets on each occasion. Frequency of ABPM (SEIVA TonoTrack) measurement was 15 min during day and 30 min during night. Patients were given preconfigured sets for HBPTM containing For a P30Plus, mobile phone and Xiaomi MiBand 2 smart wristband. 144 treated essential hypertensives aged 24–85 years, 60% males, were referred by their physicians as well controlled. Their therapy was not changed during this study. BP and HR values were accessible to patients and their physicians on a secured server. The demanded 5 minutes of physical inactivity before and during BPM were checked in informed patients by smart wristbands to increase the reliability of HBPTM. Undesired physical activity before and during BP measuring process was shown as the footmark symbol near to BP value in HBPTM logbook. Data were evaluated using a linear mixed model adjusted for gender, age, and BMI. Results: There was no significant difference in mean systolic BP (SBP) of both HBPT week cycle (132.6 ± 10.6 vs. 131.3 ± 9.9 mmHg) and daytime ABPM (135.8 ± 11.5 vs. 134.0 ± 10.6 mmHg) during the time period, respectively. Mean SBP of daytime ABPM was significantly higher (p < 0.001) compared to mean SBP of HBPTM both at entry (135.8 ± 11.5 vs. 132.6 ± 10.6 mmHg) and exit (134.0 ± 10.6 vs. 131.3 ± 9.9 mmHg). Conclusions: Mean SBP of both HBPTM and daytime ABPM were consistent during the study. Daytime ABPM was consistently significantly higher by approximately 3 mmHg compared to HBPTM with the checked 5 min rest before BPM by smart wristbands. Our results suggest, that both methods are comparable.